2014
DOI: 10.1093/nar/gku717
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Brahma complex remodels nucleosome organizations in multiple aspects

Abstract: ATP-dependent chromatin remodeling complexes regulate nucleosome organizations. In Drosophila, gene Brm encodes the core Brahma complex, the ATPase subunit of SWI/SNF class of chromatin remodelers. Its role in modulating the nucleosome landscape in vivo is unclear. In this study, we knocked down Brm in Drosophila third instar larvae to explore the changes in nucleosome profiles and global gene transcription. The results show that Brm knockdown leads to nucleosome occupancy changes throughout the entire genome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 39 publications
4
24
0
1
Order By: Relevance
“…The average nucleosome density in the gene body was similar in both clusters, as revealed by analysis of MNase-seq data produced by Shi et al. ( 4 ), but the genes of cluster 1 were characterized by a lower nucleosome density downstream of the CS (Figure 5C ), which suggests that the genes of cluster 1 generally have a more open chromatin conformation in the downstream region. We also used the data from Shi et al.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…The average nucleosome density in the gene body was similar in both clusters, as revealed by analysis of MNase-seq data produced by Shi et al. ( 4 ), but the genes of cluster 1 were characterized by a lower nucleosome density downstream of the CS (Figure 5C ), which suggests that the genes of cluster 1 generally have a more open chromatin conformation in the downstream region. We also used the data from Shi et al.…”
Section: Resultssupporting
confidence: 55%
“…The human SWI/SNF contains one of two ATPase subunits: either human BRM (hBRM) or Brahma-related gene 1 (hBRG1). The SWI/SNF complexes regulate transcription by remodeling nucleosomes at promoter regions and gene bodies ( 3 , 4 ). Genome-wide studies have revealed that SWI/SNF core subunits co-localize extensively with RNA polymerases and show high occupancy levels at promoters, enhancers and CTCF motifs ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…As an important transcription coactivator that cooperates with TFs (38), BRM is essential for the activation of homeotic genes to control early embryonic morphogenesis in Drosophila (39). Lack of brm results in nucleosome disorganization and subsequent transcription perturbations (40). Logically, miR-276 may maintain the early embryonic developmental homeostasis via modulating a suite of downstream genes of brm.…”
Section: Discussionmentioning
confidence: 99%
“…In support of our findings indicating an overall repressive role of BRM in limiting transcription output of CLK target gene promoters and its catalytic function to increase nucleosome density, recent genome-wide studies examining BRM function in D . melanogaster larval tissues [ 76 ] and primary mouse cells [ 55 ] showed that knocking down BRM led to widespread disruption of nucleosome organization, with a bias towards a decrease in nucleosome density, especially at promoters and peri-TSS regions. Furthermore, although the relationship between loss of nucleosome density upon BRM knockdown and changes in gene transcription is highly variable, more genes appeared to be significantly upregulated than downregulated, thus corresponding with our findings in Drosophila CLK target genes.…”
Section: Discussionmentioning
confidence: 99%